Combination of Ipilimumab and Adoptive Cell Therapy with Tumor-Infiltrating Lymphocytes for Patients with Metastatic Melanoma - Mullinax, John E.; Hall, MacLean; Prabhakaran, Sangeetha; Weber, Jeffrey; Khushalani, Nikhil; Eroglu, Zeynep; Brohl, Andrew S.; Markowitz, Joseph; Royster, Erica; Richards, Allison; Stark, Valerie; Zager, Jonathan S.; et al. (Frontiers in Oncology, 2018)
Purpose: Adoptive cell therapy (ACT) using tumor-infiltrating lymphocytes (TIL) for metastatic melanoma can be highly effective, but attrition due to progression before TIL administration (32% in prior institutional experience) remains a limitation. We hypothesized that combining ACT with CTLA-4 blockade would decrease attrition and allow more patients to receive TIL. Experimental Design: Thirteen patients with metastatic melanoma were enrolled. Patients received four doses of ipilimumab (3 mg/kg) beginning two weeks prior to tumor resection for TIL generation, then one week after resection, and 2 and 5 weeks after pre-conditioning chemotherapy and TIL infusion followed by IL-2. The primary endpoint was safety and feasibility. Secondary endpoints included of clinical response at 12 weeks and at one year after TIL transfer, disease free survival (DFS) and overall survival (OS). Results: All patients received at least 2 doses of ipilimumab, and 12 of the 13 (92%) received TIL. A median of 6.5x10^10 (2.3x10^10 - 1.0x10^11) TIL were infused. At 12 weeks following infusion there were 5 patients who experienced objective response (38.5%), 4 of whom continued in objective response at one year and one of which became a complete response at 52 months. Median progression-free survival was 7.3 months (95%CI 6.1-29.9 months). Grade ≥3 immune-related adverse events included hypothyroidism (3), hepatitis (2), uveitis (1) and colitis (1). Conclusions: Ipilimumab plus ACT for metastatic melanoma is feasible, well tolerated, and associated with a low rate of attrition due to progression during cell expansion. This combination approach serves as a model for future efforts to improve the efficacy of ACT.